Efficacy and safety of triple versus dual combination blood pressure-lowering drug therapy: a systematic review and meta-analysis of randomized controlled trials. Issue 8 (August 2019) - Salam, Abdul; Atkins, Emily R.; Hsu, Benjumin; Webster, Ruth; Patel, Anushka; Rodgers, Anthony
Abstract : Background and objectives: Most patients with hypertension need at least two drugs to achieve goal blood pressure. This systematic review assessed efficacy and safety of triple versus dual combination therapy for the management of hypertension. Methods: Publication databases, clinical trial registries and regulatory agency websites were searched until April 2018 for double-blind randomized controlled trials (RCTs) comparing triple with dual therapy of BP-lowering drugs, for at least 3 weeks, among patients with hypertension. Meta-analyses for efficacy and safety outcomes were performed using random-effects model. Regimen efficacy was predicted using the Therapeutic Intensity Score (TIS) and the Law et al. method (which predict dose doubling increases efficacy by 100% and around 20%, respectively), and compared with observed efficacy. Results: Fourteen RCTs (11 457 participants) were included. Overall, triple compared with dual therapy reduced BP by 5.4/3.2 mmHg ( P < 0.001), and improved BP control by 58 versus 45% [relative risk (RR) 1.33 (95% CI 1.25–1.41)], whereas incidence of withdrawals because of adverse events were 3.3 versus 3.4% [RR 1.24 (95% CI 1.00–1.54), P = 0.05]. Law et al. 's method was superior to TIS in predicting differences in efficacy between triple and dual therapies. For patients uncontrolled on submaximal dose dual therapy, adding a third drug achieved on average approximately four times more BP reduction than doubling the dose of dual therapy component drugs (6.0/3.6 versus 1.5/0.8 mmHg, respectively). Conclusion: Addition of a third drug is likely to be more efficacious without increasing adverse events, compared with increasing dose of existing dual therapy. Early use of triple therapy can significantly improve hypertension control. Abstract : Supplemental Digital Content is available in the text